Pengaruh Penerapan TQM Terhadap Performance KPI di PT KSB Sales Indonesia - Subawa, Subawa; Dewi, Colifah (JURNAL ADMINISTRASI KANTOR; Vol 12 No 1 (2024): Jurnal Administrasi Kantor (Juni 2024)DO - 10.51211/jak.v12i1.2978, 2024)
This research aims to determine the effect of implementing total quality management on PT KSB Sales Indonesia's KPI which is manifested in four principles, namely customer satisfaction, respect for everyone, management based on facts, and continuous improvement at PT KSB Sales Indonesia. The research used uses a qualitative descriptive method where interviews, observations and company documentation are the data sources. Company performance is measured by expectations regarding the conformity of the company's promise to send goods on time without product defects. Constraints. The results of the research show that there is an influence of the implementation of TQM on the company's KPI. This is proven by the achievement of KPI in customer satisfaction and the company's efforts to minimize delays in delivery of goods by 97% of target of 100% in 2020. This can be seen from the fact that there are no penalty fees charged to the company. What is obtained is that of the four TQM principles, there is one that has not yet been realized, namely in terms of company documentation where work document control does not have a standard workflow (flow chart). And the solution provided is to create a workflow for document control   Keywords : Total Quality Management, principles TQM, benefits TQM.